Use of caffeinated chewing gum as an ergogenic aid - Bellar, D.; Judge, L. W.; Craig, B. W. (Strength and Conditioning Journal, 2011)
Caffeine has many beneficial physiological and psychological effects. Customary methods of caffeine administration include ingestion either in capsule form or through consumption of caffeinated beverages. Caffeinated chewing gum is a form of caffeine administration that represents a convenient alternative delivery method based on the rapid delivery through the mucosal lining